Toward low-sensitive and high-energetic cocrystal III: thermodynamics of energetic–energetic cocrystal formation. Issue 47 (12th November 2015) - Wei, Xianfeng; Zhang, Anbang; Ma, Yu; Xue, Xianggui; Zhou, Junhong; Zhu, Yuanqiang; Zhang, Chaoyang
Abstract : Thermodynamics of the energetic–energetic cocrystal formation. Abstract : Energetic cocrystallization is a promising crystal engineering method for energetic materials. However, the current yield of energetic–energetic cocrystals (EECCs) remains very limited largely as a result of inefficient EECC screening. Therefore, the crystallization thermodynamics of EECCs must be predicted; this process is the core of the screening procedure. The present work provides insight into the intermolecular interactions of and variations in lattice energy, enthalpy, and Gibbs free energy following the crystallization of observed and supposed EECCs. Moreover, this research clarifies the difference in the solubility parameters of each pair of coformers. As a result, formation is predicted to be thermodynamically favored for most observed and supposed EECCs. The dominance of entropy is more sufficient than that of enthalpy; this dominance is mainly caused by the structural similarity in energetic molecules that either produce little heat or absorb heat if an intermolecular rearrangement is observed to transform pure crystals into cocrystals. Implicitly, EECCs can be formed efficiently when confusion degrees or spatial molecular configurations increase, thus guaranteeing entropy dominance.